2020
DOI: 10.1101/2020.05.26.20113233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude, practice and fear of COVID-19: A cross-cultural study

Abstract: Background: Knowledge, Attitude and Practice (KAP), and Fear toward COVID-19 are an important issue when designing public health approaches to control the spread of this highly contagious disease like COVID-19 during the global pandemic period. Studies with KAP and fear measures are limited only regional or country level, not yet with global or cross-cultural populations. The study is aimed to measure KAP and fear level towards COVID-19 and explore its cross-cultural variances in knowledge by socio-demographic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 19 publications
11
21
1
1
Order By: Relevance
“…In this study, the odds of positive attitude among single students was 3-folds higher compared to married students. This finding is consistent with a study conducted in eight countries of five continents [35]. Consequently, single students might have adequate time [48] This study revealed that students who were learning Diploma (TVET) level training had 73% less likely to have positive attitudes towards COVID-19 preventive measures compared to those who were learning degree program training.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, the odds of positive attitude among single students was 3-folds higher compared to married students. This finding is consistent with a study conducted in eight countries of five continents [35]. Consequently, single students might have adequate time [48] This study revealed that students who were learning Diploma (TVET) level training had 73% less likely to have positive attitudes towards COVID-19 preventive measures compared to those who were learning degree program training.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the overall good level of knowledge regarding COVID-19 pandemic among college students was 69.6%. This finding is lower than studies conducted in Debre Birhan University (73.8%) [34], eight teaching hospitals Ethiopian (88.2%) [27], Indian medical students (94.5%) [31], eight countries of five continents (80.8%) determinants [35], Malaysia (80.5%) [36], Tanzania (84.4%) [37], Sudan (90.6%) [38], Pakistan (71.5%) [28]. The discrepancy might be due to differences in cut-values used to categorize the knowledge levels, sample size, and sociocultural various between study settings.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Female participants were more likely to have adequate knowledge. This nding was surprisingly similar to a cross-cultural KAP study by Ali et al (2020). Higher education level was signi cantly associated with having adequate knowledge which can be justi ed by previous studies (Erfani et al, 2020;Farhana, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…It was in the same line with Hossain et al, [31] who reported that knowledge scores showed contrasting correlation with Fear scores. In contrast, Ali et al, [5] didn't find a correlation between fear and knowledge.…”
Section: Discussionmentioning
confidence: 85%